2018
DOI: 10.1016/j.dcn.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

From swing to cane: Sex differences of EEG resting-state temporal patterns during maturation and aging

Abstract: While many insights on brain development and aging have been gained by studying resting-state networks with fMRI, relating these changes to cognitive functions is limited by the temporal resolution of fMRI. In order to better grasp short-lasting and dynamically changing mental activities, an increasing number of studies utilize EEG to define resting-state networks, thereby often using the concept of EEG microstates. These are brief (around 100 ms) periods of stable scalp potential fields that are influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
98
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 103 publications
12
98
7
1
Order By: Relevance
“…Increases in microstate duration and decreases in occurrence were observed among older adults for all microstate configurations. These findings support and extend previous findings of age-related differences in microstate duration and occurrence (Koenig et al, 2002;Tomescu et al, 2018). In addition, we found that microstates A and B explained more variance in the EEG time series of older adults, whereas microstates C and E explained less variance, compared to the younger age group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Increases in microstate duration and decreases in occurrence were observed among older adults for all microstate configurations. These findings support and extend previous findings of age-related differences in microstate duration and occurrence (Koenig et al, 2002;Tomescu et al, 2018). In addition, we found that microstates A and B explained more variance in the EEG time series of older adults, whereas microstates C and E explained less variance, compared to the younger age group.…”
Section: Discussionsupporting
confidence: 91%
“…Reliable age-related differences have been observed across a number of neuroimaging modalities (Campbell and Schacter, 2017). On the basis of these and other studies reporting agerelated differences in microstates (i.e., Koenig et al, 2002;Tomescu et al, 2018), we also expected to find substantial age group differences in microstate dynamics. However, given the exploratory goals of the present study, we had no specific hypotheses regarding which measures of microstate temporal dynamics or microstate configurations would be associated with specific individual differences in gender, personality, mood, or attentional performance.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The topographies of these three microstates strongly resemble three of the four canonical microstates previously described in the literature (for reviews see (17,20)). Studies on large cohorts showed that microstate C is generally the most dominant state during eyes-closed rest (54). Recently, Seitzman et al (55) showed that microstate C decreases in duration and occurrence during a mental arithmetic task, similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Two temporal parameters were then quantified for each recording of each subject: the mean duration a given cluster map (microstate) was present without interruption, and the number of times per second a given microstate appeared, independent of the durationtermed "occurrence" (Michel and Koenig, 2018). In addition, we analysed the syntax of EEG microstates by computing the probabilities from a single n th -previous state to the current one for each subject and transition pair, normalized by the occurrence of each state (Lehmann et al, 2005;Tomescu et al, 2018)).…”
Section: Back-fittingmentioning
confidence: 99%